2016
DOI: 10.1007/s10068-016-0005-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of matrix effects occurred during the analysis of organochlorine pesticides in agricultural products using GC-ECD

Abstract: Matrix effects observed during the multiresidue analysis of seven organochlorine pesticides in six different agricultural products with GC-ECD were assessed. The presence of matrix coextractives, a major cause of observed matrix effects, directly and/or indirectly influenced the chromatographic responses of some pesticides. Two types of external calibrations, solvent calibration (SC) and matrixmatched calibration (MC), were used to assess matrix effects. Greater matrix effects were observed at the lower concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This is due to the presence of matrix impurities that co-elute with the analyte of interest, and interfere with the signal of the detector, resulting in signal enhancement or suppression [ 38 ]. The matrix effect has been well documented in pesticide residue analysis using GC-ECD [ 39 , 40 , 41 ]. In case of signal enhancement, recoveries above 100% will be obtained in a spiking experiment.…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the presence of matrix impurities that co-elute with the analyte of interest, and interfere with the signal of the detector, resulting in signal enhancement or suppression [ 38 ]. The matrix effect has been well documented in pesticide residue analysis using GC-ECD [ 39 , 40 , 41 ]. In case of signal enhancement, recoveries above 100% will be obtained in a spiking experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Pesticides improve and stabilize agriculture by controlling of weeds, fungi, and harmful insects. Nevertheless, it is suggested that farmers use at least pesticides with less toxicity and half-life, such as systematic pesticides [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Analytical methods for the detection of dicarboximide fungicides have been developed, such as gas chromatography–mass spectrometry (GC-MS), 8–10 gas chromatography systems equipped with electron capture detectors (GC-EDC), 11 and liquid chromatography–mass spectrometry (LC-MS). 12 In comparison, the advantages of the simpler immunoassays are significant, such as speed, cost-effectiveness, simple sample pretreatment, and the capability of high-throughput screening.…”
Section: Introductionmentioning
confidence: 99%